Loan loss provisioning and procyclicality: Evidence from an expected loss model - Christian Domikowsky; Sven Bornemann; Klaus Duellmann; Andreas Pfingsten (Deutsche Bundesbank, 2014)
Several studies have addressed, with conflicting results, the issue of procyclical effects of loan loss provisions in the past. More recently, the weak performance of incurred loss models in the financial crisis has given rise to a new debate on the sound design of credit risk provisioning schemes, which is reflected in the scheduled implementation of an expected loss model in IFRS 9. This study contributes to the extant literature by separately analyzing the cyclical effects of specific and general loan loss provisions under a legislative framework that allows provisions based on expected losses in the loan portfolio. Using three different measures of forward-looking provisioning, we find typical German banks, most of them unlisted and operating regionally, to use specific loan loss provisions countercyclically, in particular for earnings management and by anticipating non-performing loans at the closing date. The use of general loan loss provisions is predominantly motivated by tax considerations, pointing out the considerable importance of the impact of local tax law.
Keywords: G01; G21; M41; 330; procyclicality; earnings management; hidden reserves; loan loss provisioning; expected losses; managerial discretion